Talent Management in the Disruption Era: Managing Digital Competencies in Human Capital - Nada Cantika Putri Kadua (TechTalent & Business Review, 2026)
The rapid advancement of digital transformation in the era of disruption has shifted the strategic role of human resources toward competency-based talent management. Organizations are required to integrate digital competencies into their human capital strategies to remain competitive and adaptive. This study aims to analyze and develop a competency-based digital talent management model that enhances organizational adaptability and competitiveness. The research employs a qualitative descriptive approach, utilizing data collected through semi-structured interviews, document analysis, and observations. The data are analyzed using thematic analysis, including data reduction, categorization, and interpretation to identify key patterns and relationships. The findings indicate that digital competencies such as information literacy, digital communication, and problem-solving significantly influence employee performance and organizational effectiveness. In addition, the implementation of data-driven talent management strategies, including digital recruitment, continuous upskilling and reskilling, and flexible work systems, enhances workforce adaptability and engagement. Organizational support factors, such as digital leadership, adaptive culture, and agile structures, further strengthen the success of digital talent management implementation. The study concludes that integrating digital competencies into a comprehensive talent management system is essential for building a future-ready workforce and sustaining organizational competitiveness in a dynamic digital environment